Limited role of shifting cultivation in soil carbon and nutrients recovery in regenerating tropical secondary forests - Mukul, Sharif A.; Herbohn, John; Ferraren, Angela; Congdon, Robert (Frontiers in Environmental Science, 2022)
Shifting cultivation is a dominant land-use in the tropical forest-agriculture frontier in Southeast Asia and is blamed for much of the environmental degradation in the region. We examined the distribution and availability of four soil macronutrients – i.e. soil organic carbon (SOC), total nitrogen (N), phosphorus (P) and potassium (K), in secondary forests regenerating after shifting cultivation abandonment. Soil samples were collected along an upland fallow gradient on Leyte Island in the Philippines. The effect of site environmental attributes on the availability of SOC and nutrients was investigated using linear mixed-effect models. We found relatively higher concentrations of SOC and P in the oldest fallows and higher N concentration in the youngest fallow secondary forest. There was no significant difference in SOC and other macronutrients within sites of different fallow categories and soil depths, except in the case of soil K, which was highest in our control old-growth forest. Patch size together with slope of the site and fallow age were the most influential factors in explaining the variability in SOC and nutrients availability in secondary forests recovering after shifting cultivation abandonment. Our study suggests that shifting cultivation may not be detrimental to soil quality, at least on the soil parameters and soil type we studied in the Philippines upland.